The IITA Agripreneur Movement: A Dynamic Approach to Youth Empowerment across Africa - Nteranya Sanginga Dr; Adetola Adenmosun; John Obaniyi; Noel Mulinganya; Paul Woomer (Journal of International Agricultural and Extension Education, 2023)
The Agripreneur Movement of the International Institute of Tropical Agriculture (IITA) allows youth to assume their rightful place in African agricultural transformation. It started as a single exploratory agribusiness incubation at IITA Headquarters in 2012, involving 37 youths. It has since grown to 10 countries through nine sponsoring organizations. We compiled the characteristics and outcomes of 40 Agripreneur projects between 2012 and 2021 to describe the movement’s growth. With time, the movement operated across 195 locations engaging 518 trainers within 493 training cohorts and 263 different learning enterprises. These efforts led to the training of 25,616 youth in modern agriculture and agribusiness, resulting in 1,661 modernized farms and 2,592 business start-ups. Of the learning enterprises, 38% involved crops, 32% involved agro-processing, and 30% involved animal husbandry, suggesting a sound balance in promoting agribusiness opportunities. About 38.5 million was directed toward the training and support of Agripreneurs between 2012 and 2021. We trace the origins of the Agripreneur Movement as isolated agribusiness incubations in Nigeria through its expansion to other countries and its adoption within the youth empowerment agendas of other development organizations, including the African Development Bank, the International Fund for Agricultural Development, and the Mastercard Foundation. In this way, the legion of youth working with and inspired by the IITA Agripreneur Movement makes major contributions to and secures their rightful place within a complex array of rural development opportunities. What must occur next is its mainstreaming across the vocational agriculture systems and developmental sovereign loans of African countries.
Keywords: agribusiness incubation; experiential learning; International Institute of Tropical Agriculture (IITA); rural development; youth crisis